Effectiveness of Problem Based Learning (PBL) Towards Learning Outcomes Through Critical Thinking Skills - Buyung Adi Dharma; Nikmatul Tasrikah; Madziatul Churiyah (Jurnal Ad'ministrare, 2020)
The purpose of this study is to determie the effect of Problem Based Learning (PBL) on learning outcomes through critical thinking. This research is quasi experimental with posttest only control group design. Analysis of data using Two Way Anova. The result of this research shows that (1) There is a difference between students who are taught by using teaching model PBL and students who are not taught by using teaching model PBL. (2) There is a difference in learning outcomes between high critical thinking skills with low critical thinking skills. (3) There is an effect between Problem Based Learning model with the ability to think critically in learning outcomes. Keywords : Learning Model, Problem Based Learning (PBL), Learning Outcomes, Critical Thinking